Physicochemical Characteristics of Sodium Alginate Extracted from Turbinaria sp. and Sargassum sp. - Rinta Kusumawati; Jamal Basmal; Bagus Sediadi Bandol Utomo (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2018)
Characterization of sodium alginate extracted from two species of brown seaweeds (Turbinaria sp. and Sargassum sp.) harvested from Binuangeun Beach, Banten, has been conducted. The aim of the study was to evaluate physico-chemical characteristics (moisture, whiteness, viscosity, and functional groups) of sodium alginates extracted from Turbinaria sp. and Sargassum sp. Extraction was conducted in acid solution with the following steps: washing, acid extraction, bleaching, alginic acid conversion, sodium alginate conversion, dehydration, and drying. Each extraction was conducted in duplicate using approximately 1 kg of the dry raw materials (Turbinaria sp. and Sargassum sp.). Results of the analysis showed that the yield of sodium alginate powder extracted from Sargassum sp. was 24.56+0.56% (w/w) with moisture content of 12.69+1.24%; whiteness degree of 43.80+1.71%; and viscosity of 143.43+3.25 cPs, while the yield of sodium alginate powder extracted from Turbinaria sp. was 22.69+2.12% (w/w) with moisture content of 14.77+2.55%; whiteness degree of 23.77+0.68%; and viscosity of 133.67+4.04 cPs. Meanwhile, the commercial sodium alginate was identified to have moisture content of 16.07+0.09%, whiteness degree of 29.37+0.55% and viscosity of 102.67+4.04 cPs. This indicates that physicochemical characteristics of sodium alginate extracted from Sargassum sp. is better than those extracted from Turbinaria sp. and commercial alginate since it had lower moisture content as well as higher whiteness degree and viscosity.